2007
DOI: 10.1007/s00421-007-0484-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the sample collection method on salivary interleukin–6 levels in resting and post-exercise conditions

Abstract: Previous studies demonstrated that no significant relationships exist between salivary and serum IL-6 in resting conditions and following exercise and that appropriate saliva collection procedures allow to avoid analytical drawbacks. This investigation aimed to: (a) compare the effects of two methods of saliva collection on IL-6 assay; (b) search for correlation between salivary and serum IL-6 in resting and post-exercise conditions; (c) evaluate the IL-6 response to isometric contractions. Seventeen sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
(41 reference statements)
2
39
1
1
Order By: Relevance
“…Previous studies agree with the current study as they reported that salivary IL-6 level was not related to circulating IL-6 at rest and post-exercise conditions in patients and mixed gender athletes [10,15,17,18]. Moreover, it has been discovered that IL-6 mRNA are up regulated in salivary glands of mouse models [28] and in humans [29].…”
Section: Menstrual Cycle Effectssupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies agree with the current study as they reported that salivary IL-6 level was not related to circulating IL-6 at rest and post-exercise conditions in patients and mixed gender athletes [10,15,17,18]. Moreover, it has been discovered that IL-6 mRNA are up regulated in salivary glands of mouse models [28] and in humans [29].…”
Section: Menstrual Cycle Effectssupporting
confidence: 75%
“…Therefore, there is a lack of information regarding salivary IL-6 and IL-8 concentrations on resting healthy women during different phases of menstrual cycle. In addition, previous studies reported that salivary and circulating IL-6 levels do not relate to each other at rest [15,17,18] and at post-exercise [10]. Such findings need to be confirmed in healthy women at different timings of menstrual cycle to demonstrate whether salivary sampling can be employed as an alternative to blood sampling for an examination of inflammation status.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are a number of investigations, in a range of clinical settings, reporting salivary IL-6 concentrations as a good correlate of disease severity in various immune-associated conditions (Nielsen et al 2005;Rhodus et al 2005a;Streckfus et al 2001). Despite these associations, we are aware of few investigations directly comparing plasma and salivary IL-6 concentrations (Minetto et al 2005;Minetto et al 2007). If salivary IL-6 concentrations provide a valid representation of plasma IL-6, in the same way that salivary cortisol is accepted as reXecting free (unbound) plasma cortisol concentrations (Stupnicki and Obminski 1992), then this would oVer an alternative to the invasive collection procedures currently required for monitoring IL-6 responses to exercise.…”
Section: Introductionmentioning
confidence: 92%
“…Attempts have been made to detect cytokines in a variety of other body fluids using non-invasive methods including saliva (Cox et al 2008;Minetto et al 2005;Minetto et al 2007) and sweat (Cizza et al 2008;Marques-Deak et al 2006) with varying degrees of success. Saliva has been shown to be a poor medium for cytokine measurement, as there is no correlation between IL-6 concentrations in blood versus saliva either at rest (Cox et al 2008) or following strenuous exercise (Minetto et al 2005).…”
Section: Introductionmentioning
confidence: 99%